THE FORECAST OF THE DECEMBER 5, 1997, MAGNITUDE 7.8-7.9 KRONOTSKY EARTHQUAKE, KAMCHATKA, AND ITS M ≥ 6 AFTERSHOCKS - Fedotov S.A.; Chernyshev S.D.; Matvienko Yu.D.; Zharinov N.A. (My University, 1999)
Four different prediction techniques were used at the Institute of Volcanology, Far East Division, Russian Academy of Sciences, to make successful long-term and intermediate-term forecasts of the December 5, 1997, magnitude 7.8-7.9 Kronotsky earthquake, Kamchatka, and of its large (M ≥ 6) aftershocks. The prediction techniques were a long-term forecast based on seismic gap and seismic cycle properties, an M8 algorithm, repeated measurements of lengths in a geodetic network, and the use of an average M ≥ 6 aftershock sequence typical of Pacific magnitude-8 earthquakes. The forecasts are described and compared to actually observed seismicity.